2012
DOI: 10.3390/molecules17055412
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant and Immunity Function of Tetramethylpyrazine Phosphate Tablets in Vivo

Abstract: Abstract:The aim of the study was to determine the effect of tetramethylpyrazine phosphate tablets (TPT), a Chinese medicine used for cardiovascular disease, on immunity activity and oxidative injury in rats. Heart failure (HF) was induced by isoproterenol (ISO). After the animal model was established, the rats were administered the TPT by gavage (once a day). The results indicated that TPT improved left ventricular systolic pressure (LVSP), left ventricular end-diastolic pressure (LVEDP), ±dP/dt, heart weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Consistent with our findings, Guo et al also found that TET could attenuate cardiac function from myocardial injury via increasing the level of GSH and SOD and decreasing MDA. 32 These data indicated that TET could reverse BUP-induced oxidative damage in SH-SY5Y cells. However, when 3-MA was present, the level of total GS, SOD and MDA returned to the level of the BUP group.…”
Section: Discussionmentioning
confidence: 84%
“…Consistent with our findings, Guo et al also found that TET could attenuate cardiac function from myocardial injury via increasing the level of GSH and SOD and decreasing MDA. 32 These data indicated that TET could reverse BUP-induced oxidative damage in SH-SY5Y cells. However, when 3-MA was present, the level of total GS, SOD and MDA returned to the level of the BUP group.…”
Section: Discussionmentioning
confidence: 84%
“…Ligustraine is an alkaloid monomer of the plants Chuangxiong which is widely used in a variety of disease, such as cardiovascular diseases [31] . In recent years, various evidences demonstrated that ligustrazine had anti-oxidant and immunity functions [32] . Previously, we had reported that ligustrazine could suppress peritoneal brosis so as to prevent adhesion formation [19] [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Ligustrazine, also known as tetramethylpyrazine, has the molecular formula C 8 H 12 N 2 and is an identified chemical component isolated from the Chinese herb Rhizoma Chuanxiong. There are a host of clinical applications for ligustrazine, including preventing ischemic heart and cerebrovascular disease, presumably due to its documented effects on important cellular pathways, such as oxidative stress, inflammation, and angiogenesis . As the clinical indications have increased, ligustrazine's repairing effect on all kinds of trauma adhesion have gradually attracted domestic and foreign researchers .…”
Section: Introductionmentioning
confidence: 99%